Evaluating The Effectiveness Of English Language Teaching Methods In Public HEIs: A Study Literature From Sulu, Philippines - chehra nabila (Education Library, 2025)
This study evaluates and discuss of how the effectiveness from Alnakier A. Sarabi and Charisma S. Ututalum (2024) research the three methods of English teaching for instance: Grammar Translation Method, Direct Method, and Audio-Lingual Method in improving the language competence of college students in public higher education institutions (HEIs) in Sulu, Philippines. This research using the method of study literature which gathering the previous researches to answer the effectiveness of the method English teaching. By analyzing their impact on students’ proficiency in listening, speaking, reading, and writing, the study highlights how each method contributes uniquely to language learning from the sample of 200 students from HEIs in Sulu, Philippines. The results show from the research that from the three methods of teaching has a high quality in improving the student’s proficiency English Language skills. This article focuses on discussing the application effectiveness of these methods in teaching and points out the fact that these methods when used should be in moderation to promote language development across the four skills.